John Doe No. 2 and the Dreamland Motel - Womack, Kenneth (Book collections on Project MUSE., 2010)
On April 19, 1995, a truck bomb exploded just outside of Oklahoma City's Murrah Federal Building, killing 168 people. Within a matter of hours, the FBI launched the largest manhunt in U.S. history, identifying the suspects as Timothy James McVeigh and John Doe No. 2, a stocky twentysomething with a distinctive tattoo on his left arm. Eventually the FBI retracted the elusive mystery man as a bombing suspect altogether, proclaiming that McVeigh had acted alone and that John Doe No. 2 was the byproduct of unreliable eyewitness testimony in the wake of the attack. Womack recreates the events that led up to this fateful day from the perspective of John Doe No. 2--or JD, as he is referred to in the book. With his ironic and curiously detached persona, JD narrates--from a second-person point of view--his secret life with McVeigh, Terry Nichols, and others in America's militia culture as McVeigh and JD crisscross the Midwest in McVeigh's beloved Chevy Geo Spectrum. John Doe No. 2 and the Dreamland Motel is the tragicomic account of McVeigh's last desperate months of freedom as he prepared to unleash one of the deadliest acts of domestic terrorism in the nation's history. Womack's novel traces one man's downward spiral toward the act of evil that will brand his name in infamy and another's desperate hope to save his friend's soul before it's too late.